Sansevieria trifasciata Prain. : Aktivitas Antibakteri, Toksisitas, dan Prediksi ADME Senyawa In silico - Sida, Nurramdhani A.; Kasmawati, Henny (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Harapan Bersama, 2025)
Sansevieria trifasciata Prain has antibacterial activity, but this has been limited to extract and fraction samples. Nowadays, the prediction of toxicity and pharmacokinetics has not been reported. The aim of this study is to test the antibacterial activity of subfraction c of S. trifasciata Prain against S. aureus and provide in silico data on toxicity predictions and ADME profiles of the compounds within subfraction c. The antibacterial test method used microdilution, where the turbidity of each sample was tested spectrophotometrically to generate optical density (OD). Toxicity was assessed using ProTox-II, and ADME profiling was done through SwissADME. OD data were analyzed using one-way ANOVA (α0.05), and the absorbance data were visualized through Principal Component Analysis (PCA). The minimum inhibitory concentration (MIC) values for subfraction c and the positive control were 1.95 ppm and 1.95 ppm, respectively. The inhibition percentages for both treatments were 54.30% and 100%, respectively. The LD50 values for oliveramine and tricosanoic acid were 500 mg/kg (level 4) and 3200 mg/kg (level 5), respectively. Oliveramine and tricosanoic acid are toxic to the blood-brain barrier (BBB). Both compounds meet Lipinski's rules. Oliveramine has high gastrointestinal absorption, whereas tricosanoic acid has low absorption. Oliveramine shows the ability to cross the blood-brain barrier (BBB), while no permeation occurs in the brain for tricosanoic acid. Oliveramine is an inhibitor of four enzyme isoforms (CYP2C19, CYP2C9, CYP2D6, and CYP3A4), while tricosanoic acid is an inhibitor of one isoform (CYP1A2). In conclusion, subfraction c of S. trifasciata Prain can inhibit the growth of S. aureus, and the compounds suspected to play a role in this antibacterial activity are oliveramine and tricosanoic acid. Both compounds could be developed into drugs, with tricosanoic acid possibly having lower toxicity